UPAYA PENCEGAHAN MALNUTRISI ANAK MELALUI VIDEO EDUKASI PENGELOLAAN KARIES GIGI - Amalina, Rizki; Indraswary, Recita; Istiqomah, Istiqomah (Faculty of Dentistry Universitas Islam Sultan Agung, 2023)
Background: Malnutrition problem in Indonesia is still a challenge in order to improve the quality generation of Indonesian in the future. Reflecting on the 2018 Basic Health Research (Riskesdas), the prevalence of malnutrition in children in Indonesia reached 17.7 percent. One of the reasons is the increased consumption of sweet and sticky foods and drinks. The presence of children's caries can also cause psychological disturbances and pain so children have difficulty chewing food and getting inadequate nutrition. There is a need for earlier intervention through education on the need for caries management to prevent child malnutrition. This program was held to provide educational videos on caries management as an early intervention effort to prevent malnutrition in children.Method : The implementation of community service was carried out in several stages, namely: location survey, licensing, making educational videos, implementing education in the form of outreach to community cadres and preparing activity reports. Education is carried out by counselling using video media to community cadres including delivery of material, discussion (questions and answers) with resource persons and ending with conclusions and follow-up planning for implementation in the family environment.Result: The knowledge of cadre increasing because educational video can provide audio and visual illustration. Conclusion: Educational videos on caries management can be an alternative as an early intervention effort to prevent malnutrition in children.